Herbert Marcuse as Social Justice Educator : A Critical Introduction - Reitz, Charles (Routledge, 2025)
Demonstrating the continued relevance of Marcuse's work, Herbert Marcuse as Social Justice Educator details how his work remains a countervailing force to the conventional wisdom in intellectual and political matters today.
Keywords: Marcuse, Herbert, -- 1898-1979.; Social justice.; elektronické knihy; electronic books